Reimagining public understanding: Toward an institutional model - Gordon Gauchat; Kassandra Thompson (Public Understanding of Science, 2026)
Public understanding of science is often framed as either factual knowledge or generalized trust in experts. This article advances an alternative: an institutional model, grounded in cultural awareness of the norms, practices, and boundaries through which science produces credible knowledge. Existing approaches struggle to distinguish scientific controversy from broader social conflict, limiting their ability to explain why science’s legitimacy falters in politicized contexts. An institutional perspective instead shifts the focus from individual deficits to science’s role as a social system—embedded in tensions between expertise, politics, industry, and democratic accountability. We outline the implications for science communication and public engagement, arguing that meaningful participation requires not only understanding science’s institutional role in civic life but also the capacity to evaluate scientific actors against cultural expectations and normative commitments. The article concludes by proposing a research agenda centered on the cultural meaning of science and how its credibility depends on public evaluation.